2013
DOI: 10.1108/bjom-may-2012-0033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patent management effects on technological innovation performance

Abstract: Purpose -Given the changing role of patents within enterprises, this research aims to investigate the link between patent management and technological innovation performance in Chinese high-tech enterprises. Also, from theoretical underpinnings this study highlights the managerial implications of effective patent management which will lead to enhanced technological innovation performance. Design/methodology/approach -Hypotheses related to patent management and technological innovation performance in Chinese hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Sotarauta & Pulkkinen (2011) also found that KE enhances commercialisation which increases the level IP. The findings are also consistent with those of Cao & Zhao (2013) who found that KE is paramount in commercialization of innovation which enhances IP.…”
Section: Resultssupporting
confidence: 91%
“…Sotarauta & Pulkkinen (2011) also found that KE enhances commercialisation which increases the level IP. The findings are also consistent with those of Cao & Zhao (2013) who found that KE is paramount in commercialization of innovation which enhances IP.…”
Section: Resultssupporting
confidence: 91%
“…As a result, all papers that used these types of indicators have been excluded from the list. For example like patenting measure, according to [12], patent protection negatively influences the company's profit growth directly but partially mediated by commercialization. This result showed that patenting protection is only helps the commercialization process [12].…”
Section: Materials and Methodsand Methodologymentioning
confidence: 99%
“…For example like patenting measure, according to [12], patent protection negatively influences the company's profit growth directly but partially mediated by commercialization. This result showed that patenting protection is only helps the commercialization process [12]. This result concluded that the patenting is not the best indicators for innovation success; it is just as a protection for commercialization process.…”
Section: Materials and Methodsand Methodologymentioning
confidence: 99%
“…Hence, commercialization of the granted patent is the main aim to recover costs and reap profits. Highquality patent portfolios are able to appropriate the returns from commercialization [18] . If a firm owns complementary patents, these also affect the profits from technology commercialization [19] .…”
Section: Patent Commercializationmentioning
confidence: 99%